Slice scheduling strategy in LTE wireless network virtualization - Xiaodan PANG; Weiwei LI; Qian SUN; Lin TIAN (Dianxin kexue)
The future mobile communication network slicing mechanism was studied.A slice scheduler of flow level in medium access control (MAC) layer within the base station was used to utilize the shared resources between operators by predetermined proportion in the downlink LTE system.According to the different service level agreement parameters,the wireless resources are allocated for operators,which is the owner of slices in wireless network virtualization.System level simulation experiment and the comparison of the utilization between different slice methods were carried out.Compared to fixed slice method,the NVS method ensures that the users in different slices can achieve better utilization of wireless resources.In addition,the slices for services were established according to the difference of real-time(RT)and non-real-time(NRT)traffic requests,which minimizes the packet loss rate and ensures performance of the whole system.